METHODS OF FORMING EMOTIONAL INTELLIGENCE IN PRESCHOOL CHILDREN WITH SPEECH DISORDERS - Ro’ziqulova Zarina Yusuf qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
In preschool children, emotional intelligence is an important factor in the socialization of the individual, self-awareness, and effective communication with the environment. In children with speech impairments, the process of expressing emotional states, understanding the feelings of others, and responding appropriately to them becomes more complicated. This can negatively affect the child's social adaptation, relationships with peers, and psychological well-being. Speech disorders often limit the child's ability to verbally express his emotional experiences. As a result, the child may misexpress his feelings, exhibit impulsive or withdrawn behavior. Therefore, the process of forming emotional intelligence should be carried out in close connection with the development of speech.